Avaliação da ultrassonografia hepática com dopplerfluxometria em pacientes portadores de hepatite C crônica - Rocha, Haroldo Luís Oliva Gomes (2011)
INTRODUCTION: Hepatitis C is an important cause of chronic liver disease worldwide. The grading of hepatic fibrosis in chronic hepatitis C (CHC) is important for better clinical management. However, until now, liver biopsy is the only test accepted for this purpose, despite their contraindications and complications. New methods for noninvasive assessment of hepatic fibrosis are under investigation. One proposal is the Doppler ultrasound, as a noninvasive, widely available and inexpensive. OBJECTIVES: To compare laboratory parameters and liver Doppler ultrasound of patients with CHC with a healthy control group and to correlate the portal vein index (PVI), splenic index, liver histogram and hepatorenal ratio (HRR) with degrees of hepatic fibrosis. MATERIAL AND METHODS: 50 patients with CHC with liver biopsy and 44 healthy controls underwent laboratory tests and Doppler ultrasound. We evaluated several ultrasound parameters, especially maximum and minimum speed of the portal vein, PVI, pulsatility index and resistance of the hepatic artery, splenic index, liver histogram, HRR and patterns of flow velocity of the hepatic vein. Compared the means between groups and were correlated with the degree of fibrosis with sonographic parameters. We used SPSS 17 for statistical analysis. RESULTS: The groups were matched for sex and age. Of the patients who underwent biopsy, 5 (10%) had F0 fibrosis, 12 (24%) F1 fibrosis, 22 (44%) F2 fibrosis, 9 (18%) F3 fibrosis and 2 (4%) F4 fibrosis. All patients had some degree of inflammation on biopsy and only four patients had moderate or severe steatosis. There was significant difference between groups when comparing the liver enzymes AST, ALT and GGT (p<0.001), and platelets (p=0.001). There was significant difference in sonographic parameters of PVI (p<0.001), splenic index (p=0.003), liver histogram (p<0.001) and HRR (p<0.001). The triphasic pattern of supra-hepatic vein was predominant in both groups. The ultrasonographic parameters were correlated with the degree of fibrosis and plotted the ROC curve. The PVI revealed an inverse correlation of r=-0.448 (p<0.001), AUROC of 78.4% (95% CI: 68.8 to 88%) and cutoff of 0.28 (Sensibility=73.5% and Specificity=71.1%), spleen index showed a correlation of r=0.354 (p=0.001). The correlation of liver histogram was r=0.416 (p<0.001), AUROC 74.4% (95% CI: 58.5 to 90.3%), a cutoff of 77.5 (Sensibility=60% and Specificity=74.4%); The HRR was correlated with fibrosis with r=0.509 (p<0.001), AUROC of 62.4% (95% CI: 46.4 to 78.5%) and a cutoff of 1.22 (Sensibility=60% and Specificity=65.9%). None of the parameters was significant for differentiating the degree of hepatic fibrosis. CONCLUSIONS: The platelet count and liver enzymes AST, ALT and GGT were significantly different between groups of patients with CHC and control, as well as the sonographic parameters PVI, splenic index, liver histogram and HRR. There were significant and moderate correlation between fibrosis and ultrasonographic data presented previously. However these parameters were not significant in differentiating the degree of fibrosis in the group of patients with CHC.